IMPLEMENTASI METODE SMART DALAM SISTEM PENDUKUNG KEPUTUSAN PENILAIAN PRETASI BELAJAR SISWA PADA SMK MANDIRI - Rudi Bambang Herdiana; Yus Jayusman; Khoirida Aelani; Linda Hamidah (Jurnal Teknologi Informasi dan Komunikasi, 2024)
Final assessments or evaluations can help us understand if our teaching methods are working. To get the most accurate results, we need to follow specific steps and methods when evaluating student learning. Teachers can use these evaluations to find out what students are struggling with and where they need more help. Choosing the best students can be a long and difficult process, especially if it's done manually. A computer system can make this process much easier and more accurate. The biggest problem in many schools is that they don't use technology enough, especially when it comes to evaluating students. SMK Mandiri is facing this same problem. The SMART method is a good way to use technology to evaluate students. It helps us compare students based on different factors like knowledge, skills, and behavior. We used this method to evaluate 20 students at SMK Mandiri. The students were ranked based on their scores. The top 3 students had scores of 152.5, 143.75, and 141.25.